The Realities of Stranger Danger across Violent Crimes - Beatty, Jennifer (Victims & offenders, 2025)
Few crimes induce greater fear and anxiety than stranger-perpetrated violence. Although these crimes are less frequent than family or acquaintance violence, stranger-perpetrated violence encompasses much of the public discourse. The focus of this study is to understand the association between stranger, family, and acquaintance relationships across different types of violence. Utilizing data from the 2016 Survey of Prison Inmates in the United States, this study examines the association between perpetrator-victim relationships across homicide, sexual assault, robbery, and felony assault. The findings reveal most types of violence are perpetrated by family and acquaintances, not strangers.